2020
DOI: 10.3390/ijerph17249517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Prevention, and Lifestyle Intervention of Gestational Diabetes Mellitus in China

Abstract: Gestational diabetes mellitus (GDM) has become an epidemic and has caused a tremendous healthy and economic burden in China, especially after the “two-child policy” put into effect on October 2015. The prevalence of GDM has continued to increase during the past few decades and is likely to see a further rise in the future. The public health impact of GDM is becoming more apparent in China and it might lead to the development of chronic non-communicable diseases in the long-term for both mothers and their child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(151 citation statements)
references
References 74 publications
1
144
2
4
Order By: Relevance
“…Third, the prevalence of GDM in this study was lower than the overall prevalence in China (8•1 % v. 14•8 %) (2) . Previous studies have suggested that women with older age, higher pre-pregnancy BMI and a family history of diabetes are more likely to develop GDM (45,46) . However, participants in our cohort were younger, had lower pre-pregnancy BMI and less family history of diabetes than that in other populations in China (47,48) .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the prevalence of GDM in this study was lower than the overall prevalence in China (8•1 % v. 14•8 %) (2) . Previous studies have suggested that women with older age, higher pre-pregnancy BMI and a family history of diabetes are more likely to develop GDM (45,46) . However, participants in our cohort were younger, had lower pre-pregnancy BMI and less family history of diabetes than that in other populations in China (47,48) .…”
Section: Discussionmentioning
confidence: 99%
“…All pregnant women were followed up after delivery. Screening for GDM was universally performed at 24–28 gestational weeks according to Guideline for Diagnosis and Treatment of Gestational Diabetes Mellitus (2014) ( 6 ). The GDM is diagnosed if any of the oral glucose tolerance test plasma glucose values meets or exceeds the following cut-off values: 5.1 mmol/L at fasting; 10.0 mmol/L at 1 h; and 8.5 mmol/L at 2 h. The follow-up data were collected as follows: pregnant complications, gestational age, modes of delivery, 1 and 5 min Apgar scores, birth weight, placental weight, and placental volume after delivery.…”
Section: Methodsmentioning
confidence: 99%
“…GDM affects about 7% of pregnancies, where advanced maternal age, obesity, previous history of GDM, previously giving birth to macrosomic infants, and family history of diabetes mellitus are regarded as major risk factors (2)(3)(4). Oral glucose tolerance test is often used for screening GDM during 24-28 gestational weeks (5,6). However, GDM screening at 24-28 gestational weeks is too late for the physicians to make dietary or pharmacology therapy, which may ultimately affect placental integrity and fetal growth (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of gestational diabetes mellitus (GDM) has been following an increasing trend during the past few years, with available epidemiological data suggesting that it affects approximately 1 out of 7 pregnancies globally [1]. Intensive glucose control during pregnancy can substantially decrease the risk of adverse maternal, perinatal and neonatal outcomes related to GDM.…”
Section: Introductionmentioning
confidence: 99%